Size, Liquidity, and the Cost of Equity - William L. Beedles (Journal of Small Business Finance, 1991)
The inverse association of capitalization and performance is found to hold over a broader range of firms than has been previously studied. This result is found by merging data for listed United States firms with data for listed Australian companies, which are on average much smaller than their North American brethren. For the entire size spectrum and across listing locations, liquidity is found to be related to performance, adding support to the popular belief that it is (perhaps one of) the factor(s) missing from conventional tests of asset pricing. The results suggest that a lack of liquidity, rather than size per se, is a material contributor to the high cost of equity finance experienced by small companies. Some commentators attach much currency to proposals to subsidize small firms by enhancing the liquidity of their shares; the results reported here suggest that such subsidies may be effective.
Keywords: L25; G32; 650; Size; Liquidity; Cost of Equity; Cost of Capital